Bacteriostatic behavior of surface modulated silicon nitride in comparison to polyetheretherketone and titanium. Issue 5 (20th March 2017) - Bock, Ryan M.; Jones, Erin N.; Ray, Darin A.; Sonny Bal, B.; Pezzotti, Giuseppe; McEntire, Bryan J.
Abstract: Perioperative and latent infections are leading causes of revision surgery for orthopaedic devices resulting in significant increased patient care, comorbidities, and attendant costs. Identifying biomaterial surfaces that inherently resist biofilm adhesion and bacterial expression is an important emerging strategy in addressing implant‐related infections. This in vitro study was designed to compare biofilm formation on three biomaterials commonly employed in spinal fusion surgery—silicon nitride (Si3 N4 ), polyetheretherketone (PEEK), and a titanium alloy (Ti6Al4V‐ELI) —using one gram‐positive and one gram‐negative bacterial species. Disc samples from various surface treated Si3 N4, PEEK, and Ti6Al4V were inoculated with 10 5 CFU/mm 2 Staphylococcus epidermidis (ATCC®14990™) or Escherichia coli (ATCC ® 25922™) and cultured in PBS, 7% glucose, and 10% human plasma for 24 and 48 h, followed by retrieval and rinsing. Vortexed solutions were diluted, plated, and incubated at 37 °C for 24 to 48 h. Colony forming units (CFU/mm 2 ) were determined using applicable dilution factors and surface areas. A two‐tailed, heteroscedastic Student's t ‐test (95% confidence) was used to determine statistical significance. The various Si3 N4 samples showed the most favorable bacterial resistance for both bacilli tested. The mechanisms for the bacteriostatic behavior of Si3 N4 are likely due to multivariate surface effects including submicron‐topography, negative charging, and chemical interactions which form peroxynitrite (an oxidative agent). Si3 N4 is a new biomaterial with the apparent potential to inhibit biofilm formation. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1521–1534, 2017.